Sensitive surface enhanced Raman scattering multiplexed detection of matrix metalloproteinase 2 and 7 cancer markers - Gong, Tianxun (2016)
A surface enhanced Raman spectroscopy (SERS) based platform was developed for sensitive multiplexed detection of matrix metalloproteinases (MMP) (MMP-2 and MMP-7) with low limit of detection and high specificity. Detection is based on the virtue of enzymatic reaction where a peptide can be cleaved only by its corresponding enzyme. The platform comprises two components, a specialized SERS-based bimetallic-film-over-nanosphere (BMFON) substrate and gold nanoparticles (AuNPs). The two components were functionalized such that binding between the two would occur through biotin-avidin-biotin complexation. Binding is hindered by MMP peptide chains conjugated onto the surfaces of the substrate and AuNPs, and can be removed only by cleaving the peptide chains with corresponding enzymes. Since AuNP binding sites become free after the peptides are cleaved, the number of binding sites for AuNPs onto the substrate would increase. By tagging the AuNPs, concentrations of MMP-specific enzymes can be quantified through examining intensities of signature SERS peaks of the tags. This cleave-and-bind mechanism was first validated by individual detection and quantification of MMP-2 and MMP-7. The platform was demonstrated to be able to sensitively detect concentrations of specific enzymes ranging from 1 ng/mL to 40 μg/mL, with close correlation between SERS intensity and concentrations. Finally, the multiplexed detection of MMP-2 and MMP-7 was demonstrated. The multiplexity of this platform provides a robust way to analyze diseases associated with MMP-2 and MMP-7 enzymes. Our work can be further developed as a clinical diagnostic tool to detect other MMP proteinase in bio-fluids samples, widening the number of biomarkers needed to characterize diseases better